Quantitative morphometric analysis of basal forebrain neurons expressing β-nerve growth factor receptors in normal and Alzheimer's disease brains - Allen, S; Dawbarn, D; MacGowan, S; Wilcock, G; Treanor, J; Moss, T (1990)
The number and size distribution of β-nerve growth factor (β-NGF) receptor-immunoreactive neurons has been examined in the nucleus of the diagonal band and the anterior, intermediate and posterior regions of the nucleus basalis of Meynert in Alzheimer's disease (AD) and compared with normal brain. The number of neurons was in general lower in AD, although there was not a statistically significant reduction in any region of the basal nuclei. In some regions, there was an increase in the proportion of small neurons, with a decrease in larger neurons. Cortical choline acetyltransferase activity was found to correlate positively with the number of neurons in all areas of the nucleus basalis. In this group of severely demented AD patients, there was a large number of basal forebrain neurons which expressed β-NGF receptors; β-NGF may, therefore, be of therapeutic value in AD.